Drivers of e-commerce adoption amongst small & medium sized enterprises (SMEs) in the business service sector / Zahariah Mohd Zain …[et al.] - Mohd Zain, Zahariah; Jusoh, Abdul Aziz; Munir, Ros Intan Safinaz; Putit, Lennora (Universiti Teknologi MARA Shah Alam, 2020)
Technology has played a significant role in the development of business to business (B2B) or business to consumers' (B2C) electronic commerce (or e-commerce) over the recent decades. The purpose of this study is to empirically examine determinants of e-commerce adoption among small-and medium sized enterprises (SMEs) in the business services sector in a progressively developing nation. This study tested six hypotheses focusing on organizational, technological and environmental factors that may affect e-commerce adoption. Using judge mental sampling approach, a total of 110 feedback were gathered via online questionnaire based survey. The study employed SmartPLS 3.0 (Partial Least Square) structural equation modelling statistical software to confirm the hypotheses of this study. Structural model analysis was conducted and it was revealed that perceived relative advantage, perceived compatibility, e-commerce knowledge and expertise, external change agent and competitors' pressure have positive and significant influence on the SMEs respondents' e-commerce adoption. The study found that the most significant factors influencing e-commerce adoption among SMEs in Selangor was perceived relative advantage, to which managers or small and medium-sized enterprises see the potential advantage of e-commerce . The implication of this study is that SMEs need more exposure on the benefit of technology and intervention to guide them to change from traditional business to online business.